A study on the physical acceptability and antimicrobial property of the new guava ginger cloves (GGC) toothpaste formulation - Luis, Nelwina
A previous study by Aquino and Carpio proved that GGC toothpaste is a more effective antimicrobial compared to three locally available toothpaste. This study aims to formulate a GGC toothpaste with acceptable physical properties and stable antimicrobial property. Three new toothpaste formulations with varying GGC extract concentration were made and compared to the GGC toothpaste formulated by Aquino and Carpio. Thirty subjects were asked to evaluate the toothpaste (O,A,B,C) in terms of color, taste, texture, and consistency. Antimicrobial test was done through a sensitivity test wherein the zone of inhibition of two microorganisms (Strep. alpha hemolyticus and Kleb. pneumoniae) from toothpaste was measured. Results showed that the ranking of the four toothpaste from the most acceptable to the least acceptable or most unacceptable is as follows: C-B-A-O. Through the Duncan's Multiple Range Test formulations O, A and B were found to have no significant difference in terms of their antimicrobial property. Therefore improving the physical properties can only be done up to a certain limitation so as not to compromise the antimicrobial property, hence formulation B has satisfied the said objective.